Digital Supply Chain and Business Performance: The Case of the Oil and Gas Industry - Jusoh, Anis; Mahmood, Rosman; Ahmad, Zuriyati; Mohd Zahari, Ahmad Suffian (Information Management and Business Review, 2024)
A competitive global business competition requires a firm to formulate a competitive strategy in supply chain management. The transformation from manual to digital management is also necessary for the oil and gas industry. A digital supply chain is a management approach that uses technology to manage the flow of goods, information, and finance across the entire supply chain. This study attempts to evaluate the impact of the digital supply chain on business performance in the oil and gas industry. The study sample was 523 PETRONAS staff members who were involved in operating two main units, namely, a gas processing and oil refinery. The results of multiple regression analysis found that the digital supply chain significantly and positively influences firm performance across the three study samples, namely gas processing, oil refinery, and the overall sample. Technology-driven supply chain management has had a significant positive impact on every aspect of the supply chain. This can be observed in enhanced efficiency, improved visibility, time savings, and increased company competitiveness. Nonetheless, the influence of the digital supply chain is not absolute because other factors such as communication, competence, transparency, and training empirically affect the firm’s performance. All of these factors are complementary to the effectiveness of digital supply chain implementation. In line with this, steps are being taken to optimize digital applications across all aspects of the supply chain, along with certain elements related to human capital, to create a unique resource capable of fostering competitive advantage and enhancing firm performance.